DINAMIKA DAN STATUS MUTU AIR WADUK SEI NONGSA - Garno, Yudhi Soetrisno (Jurnal Teknologi Lingkungan, 2010)
Sei Nongsa is a reservoir in the Batam Industrial Development Area (BIDA), whichdeveloped especially for source of drinking water. This research was conducted toknow the water quality status of Sei Nongsa, and the suitability for the source of drinking water. This research revealed that the water of Sei Nongsa can not directly used for drinking water due to concentrations of detergent, Cu, Cr, Cd and Pb were higher than the national standard for drinking water. Base on this result, it was suggested that the water of Sei Nongsa need threatment for decrease the above parametersKey words: Nongsa, water quality status.